VIETNAMESE JOURNALISM IN ANTI-CORRUPTION - Nguyen, Tri Minh (Aliansi, 2025)
ABSTRACTThis study examines how Vietnamese journalism supports anti-corruption efforts within a media environment controlled by the state. The objective is to understand how journalists navigate censorship and institutional constraints while promoting transparency and accountability. A qualitative case study approach was employed, combining textual analysis of selected journalistic articles from major Vietnamese news outlets. The study focused on identifying rhetorical strategies, framing techniques, and thematic patterns used to report corruption-related issues. Findings reveal that Vietnamese journalists use subtle framing and strategic language to critique corruption, aligning their work with state-led anti-corruption narratives while preserving professional autonomy. Despite limited press freedom, the media plays a significant role in raising public awareness and contributing to accountability. The study recommends enhancing institutional support for investigative journalism and expanding the legal framework that protects journalistic practices in anti-corruption reporting. Further research should explore how digital platforms and transnational media collaborations can strengthen journalism’s role in governance across authoritarian contexts.